Electroclinical spectrum of the neuronal ceroid lipofuscinoses associated with CLN6 mutations. (28th July 2015) - Canafoglia, Laura; Gilioli, Isabella; Invernizzi, Federica; Sofia, Vito; Fugnanesi, Valeria; Morbin, Michela; Chiapparini, Luisa; Granata, Tiziana; Binelli, Simona; Scaioli, Vidmer; Garavaglia, Barbara; Nardocci, Nardo; et al.
<x xml:space="preserve">Abstract</x> Objectives: To describe the clinical and neurophysiologic patterns of patients with neuronal ceroid lipofuscinoses associated with CLN6 mutations. Methods: We reviewed the features of 11 patients with different ages at onset. Results: Clinical disease onset occurred within the first decade of life in 8 patients and in the second and third decades in 3. All children presented with progressive cognitive regression associated with ataxia and pyramidal and extrapyramidal signs. Recurrent seizures, visual loss, and myoclonus were mostly reported after a delay from onset; 7 children were chairbound and had severe dementia less than 4 years from onset. One child, with onset at 8 years, had a milder course. Three patients with a teenage/adult onset presented with a classic progressive myoclonic epilepsy phenotype that was preceded by learning disability in one. The EEG background was slow close to disease onset in 7 children, and later showed severe attenuation; a photoparoxysmal response (PPR) was present in all. The 3 teenage/adult patients had normal EEG background and an intense PPR. Early attenuation of the electroretinogram was seen only in children with onset younger than 5.5 years. Somatosensory evoked potentials were extremely enlarged in all patients. Conclusions: In all patients, multifocal myoclonic jerks and seizures were a key feature, but myoclonic seizures were an early and prominent sign in the teenage/adult form only. Conversely, the childhood-onset form was characterized by initial and severe cognitive impairment coupled with electroretinogram and EEG attenuation. Cortical hyperexcitability, shown by the PPR and enlarged somatosensory evoked potentials, was a universal feature.